Proceedings of the 4th International Conference on Theory and Practice of Electronic Governance 2010
DOI: 10.1145/1930321.1930336
|View full text |Cite
|
Sign up to set email alerts
|

Setback and remedy of local e-government projects

Abstract: The numbers of successful implementations of e-government projects in developing countries are noticeably low. Yet, there are few studies that focus on the long-term sustainability and success/failure factors of such projects. This paper analyzes the factors responsible for the initial success and subsequent sustainability or setback of a local-government project that was implemented in two sites in Egypt. The findings reveal that although technological, process, and structural factors play a distinctive role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…This is also supported by the cadre's statement that the immunization feature is not yet available in the system. Information systems that lack or do not provide the expected benefits can cause information system failure because there will be resistance to using the system [42]. Therefore, it is important to know the system requirements so that the system can provide benefits for IHC.…”
Section: ) Limited Access To the Internetmentioning
confidence: 99%
“…This is also supported by the cadre's statement that the immunization feature is not yet available in the system. Information systems that lack or do not provide the expected benefits can cause information system failure because there will be resistance to using the system [42]. Therefore, it is important to know the system requirements so that the system can provide benefits for IHC.…”
Section: ) Limited Access To the Internetmentioning
confidence: 99%
“…Management support has positively influenced audit technology performance among external auditors in Malaysia (Veerankutty et al, 2018). In Egypt, the successfulness of a project depends more on the top management support than technology issues (Abdelsalam et al, 2010). Jackson (1986) recommends that the involvement of top management facilitates the implementation of organisation control.…”
Section: Top Management Supportmentioning
confidence: 99%
“…Factors including technical infrastructure, financial, vision and strategy, security and privacy, good coordination, leadership, skills and change management, are amongst common factors for developing countries (Dada, 2006, Chen et al, 2006, Pudjianto & Hangjung, 2009, Gichoya, 2005, Abdallah & Fan, 2012. In addition, legal issue, human resources, lack of political will and social factor also associated with the development of e-government (Almarabeh & AbuAli, 2010, Wang & Hou, 2010, Gilbert et al, 2004, Basu, 2004, Ndou, 2004, Ebrahim & Irani, 2005, Pudjianto & Hangjung, 2009, Banerjee & Chau, 2004, Gichoya, 2005, Jorgensen & Cable, 2002, Moulder, 2001, Abdelsalam et al, 2012, Abdelsalam et al, 2010. Furthermore, research by Chen and his colleagues (2006) has identified many issues and challenges facing e-government implementation in developed and developing countries.…”
mentioning
confidence: 99%